2015
DOI: 10.1111/1751-7915.12306
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic properties of Enterococcus strains isolated from traditional naturally fermented cream in China

Abstract: SummaryThe purpose of this study was to evaluate the probiotic properties of Enterococcus strains isolated from traditional naturally fermented cream in China. Four E nterococcus isolates showed high cholesterol removal ability in media were identified as E nterococcus durans (KLDS 6.0930 and 6.0933) and E nterococcus faecalis (KLDS 6.0934 and 6.0935) by 16S rRNA and pheS gene sequences, respectively, and selected for further evaluation. In order to assess the probiotic potential and safety of these strains, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 47 publications
(52 reference statements)
4
45
0
1
Order By: Relevance
“…Despite the aforementioned cell surface factors, the genome of E. durans KLDS6.0930 also carries two fibronectin-binding proteins (LIU_RS07910 and LIU_RS10480) and an S-layer protein (LIU_RS11695), which may contribute to its adhesion. In addition, our previous study (Guo et al, 2016) showed that E. durans KLDS6.0930 could adhere to Caco-2 cells in vitro . As described below, we also demonstrated that E. durans KLDS6.0930 could colonize the cecum in vivo .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Despite the aforementioned cell surface factors, the genome of E. durans KLDS6.0930 also carries two fibronectin-binding proteins (LIU_RS07910 and LIU_RS10480) and an S-layer protein (LIU_RS11695), which may contribute to its adhesion. In addition, our previous study (Guo et al, 2016) showed that E. durans KLDS6.0930 could adhere to Caco-2 cells in vitro . As described below, we also demonstrated that E. durans KLDS6.0930 could colonize the cecum in vivo .…”
Section: Resultsmentioning
confidence: 91%
“…Minimum inhibitory concentrations (MICs) for antibiotics (ampicillin, penicillin, vancomycin, erythromycin, tetracycline, gentamicin, kanamycin, clindamycin, ciprofloxacin, trimethoprim, and rifampicin) against E. durans KLDS6.0930 were determined using a 96-well plate gradient dilution method (Guo et al, 2016a). Susceptibility was determined on the criteria adopted by European Food Safety Authority (EFSA) for the assessment of bacterial resistance to antibiotics (EFSA, 2012a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Pereira and Gibson (2002) reported high cholesterol removal ability (47%) by lactic acid bacteria and bifidobacteria isolated from human gut in broth media containing 100 µg/ml cholesterol. Guo et al (2016) reported cholesterol reduction (41.29 to 56.61%) from liquid media containing 100 µg/ml of cholesterol by Enterococcus strains. Excessive cholesterol concentration may suppress bacterial ability of cholesterol reduction.…”
Section: Resultsmentioning
confidence: 99%